Measurement of systemic risk in the Colombian banking sector - Orlando Rivera-Escobar; John Willmer Escobar; Diego Fernando Manotas (Risks, 2022)
This paper uses three methodologies for measuring the existence of systemic risk in the Colombian banking system. The determination of its existence is based on implementing three systemic risk measures widely referenced in academic works after the subprime crisis, known as CoVaR, MES and SRISK. Together, the three methodologies were implemented for the case of Colombian Banks during the 2008-2017 period. The findings allow us to establish that the Colombian banking sector did not present a systemic risk scenario, despite having suffered economic losses due to external shocks, mainly due to the subprime crisis. The results and findings show the efficiency of the systemic risk measures implemented in this study as an alternative to measure systemic risk in banking systems.
Keywords: 330; systemic risk; banking sector; DCoVaR; MES; SRISK; quantile regression; EGARCH; DCC; value at risk